Serological analysis reveals differential antibody responses between TB patients and latently infected individuals from the TB endemic country of Mozambique - Tran, Andy C.; Boariu, Eugenia; García-Bengoa, María; Kim, Mi-Young; Vergara, Emil Joseph; Mussá, Tufária; Reljic, Rajko (Frontiers in Medicine, 2023)
Serological antibody profiling of tuberculosis (TB) patients and household contacts with latent TB infection (LTBI) could identify risk indicators of disease progression, and potentially also serve as an easily accessible diagnostic tool to discriminate between these two stages of Mycobacterium tuberculosis (Mtb) infection. Yet, despite significant efforts over many decades, neither application has yet fully materialised, and this is at least in part due to inconsistent and varying antibody profiles from different TB endemic regions. In this study, we conducted a retrospective exploratory analysis of serum antibodies in a cohort of active TB patients (ATB) and their interferon-gamma release assay (IGRA) positive household contacts (LTBI), as well as healthy controls (HC) from Mozambique, a country with a high TB burden from the Sub-Saharan region. Using several Mtb antigens as well as crude preparations of culture filtrate proteins (CFP) from Mtb and Bacille Calmette Guérin (BCG), we report that the most discriminatory response for TB and LTBI was observed for serum IgA antibodies to the MPT64 antigen, followed by IgG antibodies to Ag85B and CFP, with ATB patients having significantly higher levels than LTBI or BCG-vaccinated healthy controls. Conversely, sera from LTBI individuals had higher levels of IgG antibodies to the HBHA antigen than ATB. While our sample size (n=21 for ATB, 18 for LTBI and 17 for HC) was too small to fully evaluate the diagnostic potential of these differing serological profiles, our study however preliminarily indicated high level of sensitivity (95%) and specificity (97%) of an ELISA MPT64-IgA test for discriminating TB from LTBI and healthy controls, supporting the notion that it alone, or possibly in combination with other antigens such as Ag85B or CFP could lead to development of an easily accessible diagnostic tool for TB.